Analysis of Measuring Characteristics of the Differential Pressure Water-Level Measurement System Under Depressurization Condition - Zhou, Xuwei; Cheng, Jie; She, Luchao; Fan, Guangming (Frontiers in Energy Research, 2020)
In this paper, RELAP5 code was selected to study the measuring characteristics of the double reference tube level gauge, which is commonly used in high temperature and high pressure vessels on marine nuclear power platforms, under steady and transient depressurization conditions. The response characteristics of water-level gauge, influenced by the reference cup supply water flow rate under the condition of rapid depressurization, is discussed. Measurement error and accuracy of the water-level measuring device are analyzed under both steady and transient conditions. The simulation results indicate that the relative error of the double reference tube level gauge is about 0.79% in steady state, while the measurement error is too large to accurately obtain the level in the vessel under the transient depressurization condition. However, the relative measurement error can reach about 10% under the condition of a small depressurization rate.